EFFECT OF LAND BIOPHYSICAL CONDITIONS ON LANDSLIDE VULNERABILITY IN MENOREH HILLS (CASE STUDY IN GIRITENGAH VILLAGE) - Chatarina Ganis Ratna Wardani; Hatma Suryatmojo; Sigit Heru Murti (JURNAL AGRIMENT, 2022)
Giritengah Village is one of the villages with tourism potential, strategically located in the Menoreh hills, best known for the landmass movement on Java Island. This study aimed to identify the biophysical conditions of the land that could trigger landslides in the Menoreh Hills, especially in Giritengah Village. This research was carried out in two stages divided into identifying the occurrence of landslides and identifying the land conditions. There were 33 landslides in 28 locations, with 3 locations of repeated landslides two times and 1 location of repeated landslides three times in the 2015-2021 period. Landslides In Giritengah Village are classified as shallow slides and deep slides, also a flat slip plane or translational landslide. The trend of landslides experienced a sharp increase in 2018 as many as nine events. A decrease that influenced this trend was community activity in maintaining irrigation channels. Based on the overall biophysical conditions observed and analyzed in this study, there are two patterns of landslide drift in Giritengah Village. The first pattern was a landslide at very steep slope conditions, little vegetation with low density, and not too thick soil solum. The second pattern was a landslide at steep slope conditions, thick soil solum to very thick, and lots of vegetation with medium density. These two patterns create a stronger driving force than the restraining force, making Giritengah Village a landslide-prone area.